Upper Limb Disability in Men with Combat-Related Upper Limb Injury, 8 Years Post-Injury: The ADVANCE Cohort Study - Helena Macdonald; Fraje Watson; Susie Schofield; Alexander N Bennett; Christopher J Boos; Paul Cullinan; Harriet Kemp; Nicola T Fear; Anthony M J Bull (Military Medicine, 2026)
Abstract Introduction Upper limb (UL) injuries place a considerable economic and readiness burden on the military. Long-term outcomes of UL combat-related injuries have not been examined to the same extent as those of lower limb injuries. Specifically, a better understanding of long-term outcomes following non-amputation UL injuries is essential given the crucial role of the ULs in daily activities and quality of life. This study will compare UL disability in (1) participants with UL combat injury, non-UL combat injury, and no combat injury, and (2) the presence/absence of UL injury types. This study will also describe the UL injury types sustained. Materials and Methods This study will use data from the ArmeD SerVices TrAuma RehabilitatioN OutComE (ADVANCE) study, a 20-year prospective cohort study looking at physical and psychosocial outcomes of 1,145 U.K. military personnel who served in the Afghanistan war. Approximately half of the participants sustained combat injuries including or excluding the UL [Injured-UL(Yes) or Injured-UL(No), n = 579]. At sampling, a comparison group who did not sustain combat injuries (Uninjured, n = 566) were frequency matched on age, sex, service, rank, role, and deployment period. Injured-UL(Yes) participants were grouped into injury type sub-groups (e.g., presence/absence of UL fracture). Eight years post-injury or matched deployment, participants completed the Disability Arm, Shoulder, and Hand (DASH) questionnaire, scored from 0 (no disability) to 100 (maximum disability). DASH scores were compared between groups using Mann–Whitney U and Kruskal–Wallis tests at alpha <.05. The study was approved by the U.K. Ministry of Defence Research Ethics Committee (protocol no. 357/PPE/12), and all participants provided written informed consent. Results A total of 1,132 valid DASH scores were available. Participants were 34.6 years old (SD: 5.4 years) and 7.9 years (range: 1.2-13.8 years) since injury/matched deployment. DASH scores were greater in the Injured-UL(Yes, n = 283) group than both the Injured-UL(No, n = 288) and the Uninjured groups (8.3 vs. 0.0 vs. 0.0; P < .001). Within the Injured-UL(Yes) group, DASH scores were greater in those with an artery injury (vs. no artery injury, P = .034), fracture injury (vs. no fracture, P < .001), and amputation injury (vs. no amputation injury, P = .028). The most common UL injury type was an open wound (43.1%,) followed by fractures (33.5%). Conclusions This study provides the first detailed description of the full range of UL injuries sustained in a U.K. military cohort and their long-term impact on UL disability. Participants with UL fracture, arterial, or amputation injuries reported greater levels of UL disability than those without. This study highlights the importance of considering non-amputation UL injuries alongside UL amputation injuries during the rehabilitation process to facilitate optimal long-term outcomes and potential return to service. This study is limited by the use of DASH, but ADVANCE will follow participants for the next 20 years providing increasingly rich information on UL injury outcomes. Future work should include a more focused exploration of certain UL injuries such as fractures, including their locations and any associated UL disability.